B cell depletion in immune-mediated rheumatic diseases and coronavirus disease 2019 (COVID-19) - E. L. Nasonov; A. S. Avdeeva (Научно-практическая ревматология)
In patients with immune-mеdiated (autoimmune) rheumatic diseases (IMIRD), there are a number of factors (advanced age, uncontrolled inflammation, initially irreversible damage to internal organs, comorbid pathology, genetic and other factors) that can potentially lead to an increase in “sensitivity” to SARS-CoV -2 (severe acute respiratory syndrome coronavirus-2) and concomitant viral and bacterial infections, an increase in the risk of a severe course of COVID-19 (coronavirus disease 2019), a decrease in the effectiveness of therapy for both IMIRDs and COVID-19. An important area of pharmacotherapy for IMIRDs and other autoimmune diseases is associated with the use of anti-B-cell drugs, primarily rituximab (RTX), which is a chimeric (mouse/human) monoclonal antibody (mAb) to the CD20 antigen of B cells. At present, in Russia, the RTM biosimilar, acellbia (BIOCAD), is widely used, which is not inferior to RTX in terms of efficiency and safety. The problems of anti-B-cell therapy during the COVID-19 pandemic in relation to the risk of infection, severe course and insufficient effectiveness of vaccination against SARSCoV- 2 are considered. According to the recommendations of the Association of Rheumatologists of Russia, a more rigorous assessment of indications for induction and maintenance therapy of RTX therapy and harmonization of the timing of drug administration and vaccination is required.